Formation of Plasma Around a Small Meteoroid: Simulation and Theory. Issue 5 (7th May 2018) - Sugar, G.; Oppenheim, M. M.; Dimant, Y. S.; Close, S.
Abstract: High‐power large‐aperture radars detect meteors by reflecting radio waves off dense plasma that surrounds a hypersonic meteoroid as it ablates in the Earth's atmosphere. If the plasma density profile around the meteoroid is known, the plasma's radar cross section can be used to estimate meteoroid properties such as mass, density, and composition. This paper presents head echo plasma density distributions obtained via two numerical simulations of a small ablating meteoroid and compares the results to an analytical solution found in Dimant and Oppenheim (2017a, https://doi.org/10.1002/2017JA023960, 2017b, https://doi.org/10.1002/2017JA023963 ). The first simulation allows ablated meteoroid particles to experience only a single collision to match an assumption in the analytical solution, while the second is a more realistic simulation by allowing multiple collisions. The simulation and analytical results exhibit similar plasma density distributions. At distances much less than λ T, the average distance an ablated particle travels from the meteoroid before a collision with an atmospheric particle, the plasma density falls off as 1/ R, where R is the distance from the meteoroid center. At distances substantially greater than λ T, the plasma density profile has an angular dependence, falling off as 1/ R 2 directly behind the meteoroid, 1/ R 3 in a plane perpendicular to the meteoroid's path that contains the meteoroid center, and exp [ − 1 . 5 ( R / λ T ) 2 / 3 ] / R in front of the meteoroid. When used for calculating meteoroid masses, this new plasma density model can give masses that are orders of magnitude different than masses calculated from a spherically symmetric Gaussian distribution, which has been used to calculate masses in the past. Key Points: This paper simulates the spatial distribution of the plasma density formed around a small ablating meteoroid This paper confirms the analytical expression for the spatial plasma density distribution by comparing with simulation results The new plasma distribution could result in orders of magnitude differences in head echo derived meteoroid masses from previous studies